2008
DOI: 10.1111/j.1600-0501.2007.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐induced hydrophilicity enhances initial cell behavior and early bone apposition

Abstract: The photo-induced hydrophilic surface used in the current study improves the initial cell reactions and enhances early bone apposition to the implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 29 publications
(39 reference statements)
3
113
1
1
Order By: Relevance
“…Since the method of rapid colorimetric MTT is based on metabolic cell activity, the present study results can be more reliable than those reported by Sawase et al (2008), where counting the number of adherent cells was performed by laser microscopy and specialized software; on the other hand Onuki et al (2010) detached with trypsin adherent cells and cell counting was performed with hemocytometer and finally Koseki et al (2009) isolated cells from the surface with trypsin and ultrasonic waves, those methods previously reported are ineffective for correct estimate of the number of viable cells. However, the MTT method has a limitation, minimum cells still remain on the surface, underestimation due to lack of contact time MTT reagent with cells, therefore, in future research an increase in the incubation time of the reagent with cells is recommended.…”
Section: Discussioncontrasting
confidence: 55%
“…Since the method of rapid colorimetric MTT is based on metabolic cell activity, the present study results can be more reliable than those reported by Sawase et al (2008), where counting the number of adherent cells was performed by laser microscopy and specialized software; on the other hand Onuki et al (2010) detached with trypsin adherent cells and cell counting was performed with hemocytometer and finally Koseki et al (2009) isolated cells from the surface with trypsin and ultrasonic waves, those methods previously reported are ineffective for correct estimate of the number of viable cells. However, the MTT method has a limitation, minimum cells still remain on the surface, underestimation due to lack of contact time MTT reagent with cells, therefore, in future research an increase in the incubation time of the reagent with cells is recommended.…”
Section: Discussioncontrasting
confidence: 55%
“…Sawase et al 30) found that Ti surfaces modified to attain photocatalytic hydrophilicity led to a significant increase in the attachment, spreading and proliferation of C2C12 cells, and such effects seemed to accelerate the early bone apposition to the implant surface. The present results obtained by culturing C2C12 directly on the cured materials indicate the possible advantage of Bis-GMA/TEGDMA-based composite resins or 4-META/ MMA-based resins to induce better biological responses in tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Since the surface roughness of CFRC was not significantly changed by the coating with the carbon-titanium layer, the beneficial effects of this coating on cell colonization could be explained by spontaneous oxidation of Ti and C in the cell culture system, including the formation of titanium oxides and oxygen-containing chemical functional groups. These features are known to enhance cell adhesion and growth (He et al, 2008;Sawase et al, 2008) and attract phosphate and calcium ions (Toworfe et al, 2006;Rakngarm et al, 2008), which facilitate bone tissue formation and bonding between the artificial implant and bone. Interestingly, the improvement of cell colonization by the C:Ti film was more pronounced in VSMC than in MG 63 cells, which was probably due to a different sensitivity of low-passaged cells and cell line to the physicochemical properties of the material surface.…”
Section: Amorphous Carbonmentioning
confidence: 99%